A new dual C‐shaped rectangular dielectric resonator based antenna for wideband circularly polarized radiation. Issue 6 (31st December 2018) - Kumar, Rajkishor; Nasimuddin, N.; Chaudhary, Raghvendra Kumar
Abstract: This article presents a new dual C‐shaped rectangular dielectric resonator (DR) based antenna for generation of wideband circularly polarized (CP) radiation. The proposed antenna comprises of a pair of C‐shaped rectangular dielectric DR and a metal strip with a coaxial probe. By utilization of a metal strip at the side surface of C‐shaped rectangular DR, the wideband CP radiation is achieved from the proposed dielectric resonator antenna (DRA). Fundamental orthogonal modes ( TE x δ11 and TE y 1δ1 ) are excited using the rectangular DRA with a metal strip for the generation of CP fields. The proposed antenna with dual C‐shaped rectangular CP DRA provides the measured −10 dB reflection coefficient bandwidth of 30.07% (3.22 GHz‐4.36 GHz) with measured 3‐dB axial ratio bandwidth of 14.81% (3.25 GHz‐3.77 GHz) at the boresight. The proposed antenna covers the useful Wi‐MAX band.